Answer:
b: elimination
Step-by-step explanation:
My vote is for elimination, though any of these methods (and some not listed) will get an answer quickly.
Subtracting the second equation from twice the first gives ...
2(9x +8y) -(18x -15y) = 2(7) -(14)
31y = 0 . . . simplify
y = 0 . . . . . divide by 31 (or invoke the zero-product rule)
Then the value of x can be found from the first equation:
9x = 7
x = 7/9
__
I like this method because it tells you that y=0 in one step. (Graphing does the same.) For the numbers here, you can do it mentally. Once you recognize that the x-coefficients and the constants are related by the same factor, and that factor is different for the y-coefficients, it becomes apparent that elimination will immediately tell you that y=0.